2013
DOI: 10.3390/ijms140918024
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Changes in Inflammatory and Matrix Adherence of Bronchial Epithelial Cells with Persistent Respiratory Syncytial Virus (RSV) Infection (Progressive Changes in RSV Infection)

Abstract: In addition to the acute manifestations of respiratory syncytial virus (RSV), persistent infection may be associated with long-term complications in the development of chronic respiratory diseases. To understand the mechanisms underlying RSV-induced long-term consequences, we established an in vitro RSV (strain A2) infection model using human bronchial epithelial (16HBE) cells that persists over four generations and analyzed cell inflammation and matrix adherence. Cells infected with RSV at multiplicity of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Supernatants from cells with persistent infection produced virus plaques at a reduced level, perhaps due to the generation of defective interfering particles (DIPs) (20,21). Persistent infection by respiratory syncytial virus (RSV) and coxsackie B virus (CVB) upregulates adhesion molecules and proinflammatory cytokines (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Supernatants from cells with persistent infection produced virus plaques at a reduced level, perhaps due to the generation of defective interfering particles (DIPs) (20,21). Persistent infection by respiratory syncytial virus (RSV) and coxsackie B virus (CVB) upregulates adhesion molecules and proinflammatory cytokines (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although these cells are not fully differentiated, previous studies showed that 16HBE14o-cell line can be a promising alternative to primary NHBE in some experimental models e.g. in virus infection studies (Liu et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Following 2 days in culture, the cells at 90% confluence were infected with RSV at a multiplicity of infection (MOI) of 0.01. The infected cells were collected after 3 days, when the cells exhibited a healthy cell monolayer morphology ( 10 ), and after 7 days, when a number of small syncytia began to form. In addition, a separate group of 16HBE cells were treated using the same procedure, but with uninfected HeLa cell lysate, and were used as a mock control group.…”
Section: Methodsmentioning
confidence: 99%
“…The airway epithelium is central in initiating pulmonary inflammation, particularly in the case of RSV, as this virus productively replicates only in the respiratory mucosa ( 4 , 5 ). Enzymes involved in degradation of the extracellular matrix, which have a number of important physiological effects, including remodeling of the extracellular matrix, facilitating cell migration, cleaving cytokines and activating defensins, may be important in initiating pulmonary diseases ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%